ANALISIS KOMUNIKASI PEMASARAN DALAM MENARIK PENGUNJUNG (STUDI PADA KAMPOENG KOPI BANARAN, PT. PERKEBUNAN NUSANTARA IX KABUPATEN SEMARANG) - EUNIKE SIPAYUNG; SONY HERU PRIYANTO (JURNAL ILMIAH AGRINECA, 2019)
This research was conducted in Kampoeng Kopi Banaran (Kakoba), an agrotourism owned by PT. Perkebunan Nusantara IX (Persero) located in the area of coffee plantation Getas Afdeling Assinan, Jl. Raya Semarang – Solo KM 1,5. Thisresearch aims to: (1) knowing Kakoba’s marketing communication (2) knowing the changing and factors affecting Kakoba’s marketing communications(3) knowing the impact of Kakoba’s marketing communication changes in attracting visitors. This research was conducted on February – March 2018. The participants of this research were the management of Kakoba. Data collection techniques used were observation, interviews, and study documentation.This study used a qualitative approach with descriptive design.The research results explain Kakoba marketing communication strategies are: advertising, direct marketing, and sales promotion. There is one discovery about marketing communication strategy: private relation. There are other types of communication: physical environment and quality of services that support the delivery of messages to visitors. Factors affecting the changing of marketing communications in Kampoeng Kopi Banaran is technology and information, as well as the better assessment and consumer knowledge. The impact of agrotourism marketing communication changes in Kakoba is the increasing number of visitors from year to year.